PENGEMBANGAN MODUL KEANEKARAGAMAN AVES SEBAGAI SUMBER BELAJAR BIOLOGI - Herawati, Herawati (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2016)
The objective of this research were: (1) To make module of Aves bio diversity as biology learning source; (2) To develop module of Aves bio-diversity  as biology learning source; (3)  To find out the appropriateness of module of Aves bio-diversity as a biology learning source. The population in this research was all grade X students in State Senior High School 5 in Metro. The samples were grade X students taken randomly. The data were collected with interviews, questionnaires, and observations. Analysis was conducted with questionnaires of expert, teachers, and students. Based on scale little test result and scale expanded test of students showed was very good  (82 %), this module was effective and appropriate for used as one of biology learning sources for grade X, especially in leraning Aves material in Kingdom Animalia.